2014
DOI: 10.1074/mcp.m113.037259
|View full text |Cite
|
Sign up to set email alerts
|

Colonization State Influences the Hemocyte Proteome in a Beneficial Squid–Vibrio Symbiosis

Abstract: The squid Euprymna scolopes and the luminescent bacterium Vibrio fischeri form a highly specific beneficial light organ symbiosis. Not only does the host have to select V. fischeri from the environment, but it must also prevent subsequent colonization by non-symbiotic microorganisms. Host macrophage-like hemocytes are believed to play a role in mediating the symbiosis with V. fischeri. Previous studies have shown that the colonization state of the light organ influences the host's hemocyte response to the symb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 76 publications
0
41
0
Order By: Relevance
“…Hemocytes have also been shown to internalize OMVs (Aschtgen et al, 2016) but how these vesicles and other MAMPs are detected by hemocytes is unclear. These cells do express a number of PRRs, including peptidoglycan recognition proteins (PGRPs), a Toll-like receptor (TLR), and galectins (see below; Collins et al, 2012a; Schleicher et al, 2014). The role of hemocytes in light organ development is not completely understood, but these cells are hypothesized to be involved in restructuring of the ciliated appendages during morphogenesis and after the initiation of symbiosis (Koropatnick et al, 2007).…”
Section: Hemocyte Interactions With V Fischerimentioning
confidence: 99%
See 4 more Smart Citations
“…Hemocytes have also been shown to internalize OMVs (Aschtgen et al, 2016) but how these vesicles and other MAMPs are detected by hemocytes is unclear. These cells do express a number of PRRs, including peptidoglycan recognition proteins (PGRPs), a Toll-like receptor (TLR), and galectins (see below; Collins et al, 2012a; Schleicher et al, 2014). The role of hemocytes in light organ development is not completely understood, but these cells are hypothesized to be involved in restructuring of the ciliated appendages during morphogenesis and after the initiation of symbiosis (Koropatnick et al, 2007).…”
Section: Hemocyte Interactions With V Fischerimentioning
confidence: 99%
“…The role of hemocytes in light organ development is not completely understood, but these cells are hypothesized to be involved in restructuring of the ciliated appendages during morphogenesis and after the initiation of symbiosis (Koropatnick et al, 2007). A previous study implicated that gelanolytic activity via a matrix metalloproteinase (MMP) may contribute to this process (Koropatnick et al, 2014) and other work has shown an increase in MMP expression in the light organs of colonized juveniles (Chun et al, 2008) and in hemocytes from symbiotic compared to antibiotic-treated (cured) adult hosts (Collins et al, 2012a; Schleicher et al, 2014). However, regression of the ciliated appendages may not be entirely dependent upon hemocytes, as squid colonized by V. fischeri in simulated microgravity showed a decrease in hemocyte trafficking but an accelerated restructuring of the ciliated appendages (Foster et al, 2013).…”
Section: Hemocyte Interactions With V Fischerimentioning
confidence: 99%
See 3 more Smart Citations